2019
DOI: 10.2147/ijn.s192214
|View full text |Cite
|
Sign up to set email alerts
|

<p>Plasma protein adsorption on Fe<sub>3</sub>O<sub>4</sub>-PEG nanoparticles activates the complement system and induces an inflammatory response</p>

Abstract: Background: Understanding of iron oxide nanoparticles (IONP) interaction with the body milieu is crucial to guarantee their efficiency and biocompatibility in nanomedicine. Polymer coating to IONP, with polyethyleneglycol (PEG) and polyvinylpyrrolidone (PVP), is an accepted strategy to prevent toxicity and excessive protein binding. Aim: The aim of this study was to investigate the feature of IONP adsorption of complement proteins, their activation and consequent inflammatory response as a strategy to further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…The enhanced capture of smaller PEG(+) MNPs may be attributed to the PEG–plasma protein interaction and then agglomerate formation, resulting in an increased hydrodynamic diameter of MNPs. It has been recently demonstrated that plasma protein adsorption of PEG(+) MNPs, but not bare MNPs, triggers complement activation,56 which may consequently alter protein corona composition, physical characteristics and particle behaviors in circulation. For larger MNPs, PEGylation may reduce particle–particle interaction induced by magnetic moment generation in magnetic field, and thus enhance MNP escape, allowing dynamic retention of MNPs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced capture of smaller PEG(+) MNPs may be attributed to the PEG–plasma protein interaction and then agglomerate formation, resulting in an increased hydrodynamic diameter of MNPs. It has been recently demonstrated that plasma protein adsorption of PEG(+) MNPs, but not bare MNPs, triggers complement activation,56 which may consequently alter protein corona composition, physical characteristics and particle behaviors in circulation. For larger MNPs, PEGylation may reduce particle–particle interaction induced by magnetic moment generation in magnetic field, and thus enhance MNP escape, allowing dynamic retention of MNPs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, immunotoxicity is one of the main toxicity of ENPs induced by PC in body. For example, PEG-coated iron oxide NPs (IONP-PEG) can trigger complement activation and induces an inflammatory response (increased in proinflammatory cytokines such as IL-1β, IL-6, and TNF-α) ( Rivera et al, 2019 ). Magnetic nanoparticle (MNP)-infiltrated bone regeneration scaffolds could also adsorb inflammatory related protein such as alpha-2-HS-glycoprotein, haptoglobin, and complement components, which can activate the immune system ( Figure 2A ; Zhu et al, 2019 ).…”
Section: Impacts Of In Vivo Pc On Biobehaviors Of mentioning
confidence: 99%
“…The biomolecular corona must be taken into account when considering the intrinsic biological effects that IONPs can produce. Indeed, Escamilla-Rivera et al found that PEG-coated IONPs absorb a wide variety of complement recognition proteins when incubated with human serum, leading to complement activation when injected in mice [ 95 ]. Similarly, Zhu et al demonstrated that the addition of IONPs to the hyaluronic acid (HA) scaffold enhances osteogenesis in vivo, most likely mediated by a dynamic formation of a protein corona enriched in complement-, wound healing-, and inflammatory-related factors [ 96 ].…”
Section: Iron Oxide Nanoparticle Biodegradationmentioning
confidence: 99%